The subtypes of developmental coordination disorder. (16th May 2022) - Lust, Jessica M.; Steenbergen, Bert; Diepstraten, Johanna (Ankie) E. M.; Wilson, Peter H.; Schoemaker, Marina M.; Poelma, Margriet J.
Abstract: Aim: To identify subtypes in a large group of children clinically diagnosed with developmental coordination disorder (DCD) based on their pattern of motor, cognitive, and visual‐motor abilities. Method: Standardized scores for verbal IQ, total IQ, Movement Assessment Battery for Children, Second Edition (MABC‐2) balance, MABC‐2 manual dexterity, MABC‐2 ball skills, and Beery‐Buktenica Developmental Tests of Visual‐Motor Integration (Beery‐VMI), Motor Coordination (Beery‐MC), and Visual Perception (Beery‐VP) were used. The NbClust complete procedure was used to best partition the data on 98 children (84 males, 14 females, mean [SD] age: 8 years [2 years 1 month]) into clusters. Deviation contrasts, multivariate analysis of variance, and post hoc comparisons were used to characterize the clusters. Results: Four clusters were revealed: two clusters with a broad motor skill problem, one with relatively preserved visual‐motor integration and Beery‐MC skills, and a second with abnormal ball skills, balance, and Beery‐MC skills. A third cluster with more specific gross‐motor problems, and a fourth with relatively preserved ball skills but low Beery‐MC and performance IQ, were identified. Balance scores were 'at risk' or 'abnormal' in all four clusters. Interpretation: DCD is a heterogeneous condition. However, subtypes can be discriminated on the basis of more severe difficulties in fine‐motor performance, gross‐motor performance, or both. There was evidence for generalized motor impairments in around half of all children. Importantly, at least borderline level reduced balance was evident in each subtype. What this paper adds: Four subtypes were identified in a large clinical group of children with developmental coordination disorder (DCD). Subtypes were based on motor, cognitive, and visual‐motor abilities. There was evidence of generalized motor impairments in around 50% of children with DCD. A generalized balance problem is present across all subtypes of DCD. What this paper adds: Four subtypes were identified in a large clinical group of children with developmental coordination disorder (DCD). Subtypes were based on motor, cognitive, and visual‐motor abilities. There was evidence of generalized motor impairments in around 50% of children with DCD. A generalized balance problem is present across all subtypes of DCD. This original article is commented on by Green on pages 1316–1317 of this issue.